Affirmation of a Discipline: Ephemeral Tectonics of an Architecture Lesson (EAAE Annual Conference Proceedings, 2023)
Architecture study teaching process is technical, and exact, where architecture is measurable. But architecture studies must remain open to processing abstract values itself. Architecture is rigorous but anexact*. Presented course units encourage work on elaborate execution of an ephemeral idea.